Landmark Technique vs Ultrasound Guided Approach for Posterior Tibial Nerve Block in Cadaver Models. Issue 4 (16th October 2019) - Morris, Sara Elizabeth; McKissack, Haley; Moraes, Leonardo V. M.; Viner, Gean C.; Jones, James R.; Tedder, Chandler; Kukreja, Promil; Chinnakkannu, Karthikeyan; Jha, Aaradhana J.; Shah, Ashish B.
Category: Ankle, Basic Sciences/Biologics Introduction/Purpose: Until recently, many regional anesthetic blocks were performed without the assistance of ultrasound, relying on methods such as anatomical landmarks and nerve stimulation. The use of ultrasound for peripheral nerve blocks has proven extremely useful for improving the efficacy of many regional anesthetic techniques. There remain a few nerve blocks which have lagged in employing the assistance of ultrasound consistently, one of which is the ankle block. This block is commonly utilized for either surgical anesthesia or post-operative analgesia for a variety of foot and ankle procedures. In this study, we compared the accuracy of traditional landmark technique with an ultrasound guided approach for ankle block by assessing the spread of injectate (dye) along the posterior tibial nerve (PTN) in cadaver models. Methods: Ten below-knee cadaver specimens were used for this study. Five were randomly chosen to undergo landmark guided PTN blocks, and five were selected for ultrasound-guided PTN blocks. The landmark technique was performed by identifying the medial malleolus and Achilles tendon and inserting the needle (4 cm long, 21G Braun® Stimuplex) at the midpoint of the two structures, aiming toward the medial malleolus and advancing until bone was contacted. 2 cc of blue acrylic dye was injected at this location. The ultrasound technique was performed with a linear probe identifying the medial malleolus and the PTN. The needle was advanced in-plane with a posterior to anterior trajectory until the tip of the needle was adjacent to the nerve. 2 cc of blue acrylic dye was injected surrounding the nerve. The extremities were then dissected to determine which nerves had been coated with dye. Results: 100% of the ultrasound guided blocks resulted in completely stained PTN with dye. In the landmark group, only 40% of the landmark technique blocks resulted in completely stained PTN with dye. Of the nerves not stained with dye, 2 were noted to have had dye injected posterior to the nerve and 1 was noted to have had dye injected into the flexor digitorum longus tendon. Conclusion: The base of evidence has dramatically increased in recent years in support of the use of ultrasound in regional anesthesia. This study substantiates the superiority of ultrasound guidance for ankle block by demonstrating a 100% success rate amongst the ultrasound guided group.